STRATEGI DINAS KOPERASI DAN UMKM DALAM PENGEMBANGAN UMKM DI KOTA TARUTUNG TAPANULI UTARA - Purba, Gress Sanita Dewi H; Primawati, L. Degodona; Rajagukguk, Jonson (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to determine the strategy of the Cooperative and UMKM Service in the Development of UMKM in Tarutung City as many as 70,391 UMKM consisting of various types of UMKM businesses, namely industrial and UMKM types, trade types of North Tapanuli Regency, UMKM in the agricultural sector, UMKM in the health sector and MMKM in other fields. This type of research is qualitative descriptive, the informants of this study consist of key informants, main informants, additional informants, the types of data used are primary data and secondary data. Data collection techniques are by interview and documentation. The data analysis method used is data reduction, data presentation and drawing and drawing conclusions in smaller units, looking for patterns and similar themes. The results of this study indicate that the strategies implemented by the Tarutung City Cooperative and UMKM Service to develop UMKM are by promoting products, empowerment strategies implemented for UMKM by developing entrepreneurship and competitive advantages, protection strategies implemented for UMKM by facilitating UMKM actors and providing capital assistance. The results of the Strategy of the Tarutung City Cooperative and UMKM Service in developing UMKM are increasing turnover, increasing human resource capabilities for UMKM actors and helping UMKM in developing their businesses by providing capital assistance.